Precocious Metamorphosis of Silkworm Larvae Infected by BmNPV in the Latter Half of the Fifth Instar - Xu, Ping-Zhen; Zhang, Mei-Rong; Wang, Xue-Yang; Wu, Yang-Chun (Frontiers in Physiology, 2021)
The silkworm, Bombyx mori, is a complete metamorphosis insect and an economically important for silk production, the model to study insect physiology and biochemistry. Bombyx mori nucleopolyhedrovirus (BmNPV) is a principal pathogen of the silkworm and its host range is restricted to silkworm larvae, requiring interaction with silkworm larvae to accomplish virus replication. Prothoracic glands (PGs) are a model for synthetic ecdysone with regulating insect growth and development. In this study, day-4 fifth instar silkworm larvae were infected by BmNPV, the wandering silkworms appeared in the infected groups were 12 hours earlier than that in the control groups, and the ecdysone titer in infected larvae was significantly higher than that of the control larvae. Then, we used RNA sequencing (RNA-seq) to analyze silkworm PGs 48 h after BmNPV infection. The classifications of the 15 differential expression genes (DEGs) were mainly involved in the metabolic processes and pathways. The RT-qPCR results of the DEGs in the PGs of BmNPV-infected at 24, 48, and 72 h were generally consistent with the transcriptome data. The transcripts of BmTrypsin-1 and BmACSS3 were significantly increased from 24 to 72 h after BmNPV infection that they may be involved in the maturation process in the latter half of silkworm fifth instar larvae. These findings will help to address the interactions between BmNPV infection and host developmental response.